Collapse assessment of low-rise reinforced concrete special moment resisting frame systems using a simplified method. (April 2022) - Malla, Niraj; Wijeyewickrema, Anil C.
Highlights: A simplified method is proposed to generate collapse fragility curves for low-rise special moment resisting frame (SMRF) systems. Capacity curves are developed without carrying out structural modeling and nonlinear static analysis, to obtain equivalent SDOF parameters. Ground motion spectra that matches the conditional spectrum (CS) at specified seismic intensity levels are statistically generated and a displacement-based assessment procedure instead of nonlinear response history analysis (NLRHA) is adopted, to obtain the peak displacements necessary for the generation of collapse fragility curves, with and without considering uncertainty in modeling parameters. The proposed simplified method is applied to 3- and 5-story low-rise SMRF systems for the generation of collapse fragility curves. In addition, a 8-story SMRF system is considered to examine the applicability of the proposed simplified method to non low-rise SMRF systems. Abstract: In this study, a simplified method is proposed to generate collapse fragility curves for low-rise reinforced concrete special moment resisting frame (SMRF) systems. Capacity curves are developed without carrying out structural modeling and nonlinear static analysis, to obtain equivalent SDOF parameters. Ground motion spectra that matches the conditional spectrum (CS) at specified seismic intensity levels are statistically generated and a displacement-based assessment procedure instead of nonlinear response history analysis (NLRHA) is adopted, to obtain the peak displacements necessary for the generation of collapse fragility curves, with and without considering uncertainty in modeling parameters. The proposed simplified method is applied to 3- and 5-story low-rise reinforced concrete SMRF systems for the generation of collapse fragility curves. In addition, a 8-story reinforced concrete SMRF system is considered to examine the applicability of the proposed simplified method to non low-rise reinforced concrete SMRF systems. The results show that the collapse fragility curves generated by using the proposed simplified method are in good agreement with the curves developed using NLRHA for the 3- and 5-story low-rise reinforced concrete SMRF systems; however, such agreement is not observed for the 8-story non low-rise reinforced concrete SMRF system.